ОСОБЕННОСТИ ИНФИЛЬТРАЦИОННОГО УВЛАЖНЕНИЯ ГРУНТОВ ИЗ КАНАЛОВ И СООРУЖЕНИЙ НА НИХ - Хужакулов, Р.; Джуманазарова, А.; Жаксымуратов, К.; Базарбаев, М. (SCIENCE and SOCIETY, 2019)
The article deals with the features of the infiltration moistening of soils from canals and structures on them. Based on the analysis of previous studies performed, the specificity of infiltration in loess soils is considered as a serious factor affecting the stress-deformative state of hydraulic structures and their foundations.
Keywords: subsidence soil; infiltration; degree of humidity; calculation of deformations; hydraulic structures; loess grounds; the process of moistening; terms of preliminary soaking